Relationship between Total Session of Hyperbaric Oxygen Therapy as Adjuvant Therapy with Diabetic Foot Ulcers Improvement in Dr. Mintohardjo Naval Hospital in The Year 2016−2018 - Andrisha, Naufal Hilmi; Savitri, Pritha Maya; Bustamam, Nurfitri (UI Scholars Hub, 2020)
Introduction. Diabetic foot ulcers (DFU) are a common complication of diabetes mellitus (DM). High rates of amputation risk and mortality in DM patients with DFU as well as the use of conventional therapies that often fail to improve the DFU condition cause an adjuvant therapy such as hyperbaric oxygen therapy (HBOT) to be used. HBOT is known can facilitate wound bed closure and reduce the amputation rates in diabetic gangrene foot. This study aimed to determine the relationship between total sessions of HBOT as adjuvant therapy with an improvement of DFU patients. Method. A cross-sectional study was conducted among DFU patients who were given HBOT as adjuvant therapy in Dr. Mintohardjo Naval Hospital in the year 2016–2018. Data were collected from the medical record. The statistical analysis used in this study was the Friedman test to assess whether there was a relationship between the total session of HBOT with the DFU improvement. Wilcoxon post-hoc test was performed to provide the treatment group with the best DFU improvement. Results. There were 20 subjects in this study. To assess the best treatment group in DFU improvement, a comparison between the treatment groups under 10 sessions and above 10 sessions with other treatment groups was made. Friedman test with p-value = 0,001 indicates that there was a relationship between total session of HBOT as adjuvant therapy with an improvement of DFU. Based on Wilcoxon post-hoc test, the treatment groups that were statistically significant in DFU improvement was a treatment group above 10 sessions with p-value = 0,001. Conclusion. The total session of HBOT as adjuvant therapy above 10 shows that it is the most significant improvement for DFU with a decrease in the ulcer degree and reduced wound size.